Insider-outsider view of social work curricula in Estonia - should one competence of future social workers be policy literacy? - Reeli Sirotkina; Kersti Kriisk (Social Work & Society, 2022)
This article focuses on the development of social policy and social work curriculum from the perspective of the programme leaders. Analysing the social work curriculum development between 1991-2020, as insiders and outsiders, we explore the process of positioning social policy within the social work curricula. Social work and social policy have been complementing each other in the field and in the training of social workers. Constructivist grounded theory approach was insightful in showing what was hindering the decisions of social work programme leaders. It also showed how the long-term impact of the Bologna process, the growing role of interdisciplinarity, competition in higher education and the programme managers personal opinions, together with the definition of social policy and social work, influence the design of the social work curricula. The article emphasises the role of programme leaders and the reforms of higher education in the curriculum development process. Therefore, how to bridge the complexity in curriculum development will remain a challenge for social work academics and require more future analysis and research.